1993
DOI: 10.1200/jco.1993.11.5.873
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cisplatin intensity in metastatic non-small-cell lung cancer: a phase III study of the Southwest Oncology Group.

Abstract: This study does not confirm evidence of a steep clinical dose-response curve for cisplatin in NSCLC at the cisplatin dose-intensities achieved. The addition of mitomycin increases the response rate, but does not improve survival. Continued evaluation of new agents in this disease is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…10 randomized trials comparing a basic chemotherapy regimen with or without MMC (Einhorn et al, 1986;Crino et al, 1988Crino et al, , 1990Bonomi et al, 1989, Luedke et al, 1990Fukuoka et al, 1991;Shinkai et al, 1991;Weick et al, 1991;Mylonakis et al, 1992;Gandara et al, 1993;Masutani et al, 1996) were available for a metaanalysis. Their main characteristics and results are summarized in Table 2 8 of them included more than 2 arms but we considered only the 2 arms of interest, leading to a total of 1769 eligible patients, 876 treated in the experimental arm with MMC and 893 in the control arm without MMC.…”
Section: Question 2: Does MMC Improve the Results When Added To Othermentioning
confidence: 99%
See 1 more Smart Citation
“…10 randomized trials comparing a basic chemotherapy regimen with or without MMC (Einhorn et al, 1986;Crino et al, 1988Crino et al, , 1990Bonomi et al, 1989, Luedke et al, 1990Fukuoka et al, 1991;Shinkai et al, 1991;Weick et al, 1991;Mylonakis et al, 1992;Gandara et al, 1993;Masutani et al, 1996) were available for a metaanalysis. Their main characteristics and results are summarized in Table 2 8 of them included more than 2 arms but we considered only the 2 arms of interest, leading to a total of 1769 eligible patients, 876 treated in the experimental arm with MMC and 893 in the control arm without MMC.…”
Section: Question 2: Does MMC Improve the Results When Added To Othermentioning
confidence: 99%
“…Einhorn, 1986Crino, 1988-90 Bonomi, 1990Luedke, 1990Fukuoka, 1991Shinkai, 1991Weick, 1991Mylonakis, 1992 Gandara, 1993 Crino, 1988−90 Bonomi, 1990Luedke, 1990Fukuoka, 1991Shinkai, 1991Weick, 1991Mylonakis, 1992Gandara, 1993Masutani, 1996 OVERALL 0.0 1.3 2.5 3.75 5.0 On the 4 prospective phase II trials found in the literature (Table 4), 3 deal with a combination of MMC with vindesine (Kris et al, 1985;Sculier et al, 1986, Bonomi et al, 1989) and 1 with cisplatin and vinblastine (Gridelli et al, 1992). The ELCWP quality score for phase II trials ranged from 21.1% to 75% with a median of 61.1%.…”
Section: Question 2: Does MMC Improve the Results When Added To Othermentioning
confidence: 99%
“…Cisplatin has been used in combinations with other different chemotherapeutic agents, such as DNA-alkylators, topoisomerase II inhibitors, vinorelbine and gemcitabine (Fukuoka et al, 1992;Liu, 1993;Sculier et al, 1994;Gridelli et al, 1996;Wozniak et al, 1998;Lippe et al, 1999). Besides evaluation of different combinations of cisplatin, important other approaches have focused on increasing the dose and/or the dose intensity of the drug using higher doses per course (Klastersky et al, 1986;Gandara et al, 1993), or shortening the treatment interval (Planting et al, 1993(Planting et al, , 1994(Planting et al, , 1995a(Planting et al, , b, 1996a(Planting et al, , b, 1997(Planting et al, , 1999. Cisplatin when applied as a single agent at a 3-or 4-weekly schedule and a dose of 100 mg m À2 has a low activity in advanced NSCLC and the overall response rate (RR) varies from 12 to 15% (Gandara et al, 1993;Wozniak et al, 1999).…”
mentioning
confidence: 99%
“…The use of higher cisplatin doses was based on one small randomized trial that demonstrated longer duration of response and a survival advantage for responders in the higher dose arm, but no overall survival results were reported (Gralla et al, 1981). However, three subsequent larger randomized studies have failed to show advantage for the higher cisplatin doses, and toxicity was considerably worse (Klastersky et al, 1986;Gandara, 1993;Felip et al, 1997).The first randomized study using new agents compared vinorelbine/cisplatin to vindesine/cisplatin to vinorelbine alone in 612 patients. The vinorelbine/cisplatin combination resulted in a significantly superior response rate (30% vs 19% vs 14%), survival (median survival in weeks 40 vs 32 vs 31) and 1-year survival (35% vs 27% vs 30%) (Le Chevalier et al, 1996).…”
mentioning
confidence: 99%
“…The use of higher cisplatin doses was based on one small randomized trial that demonstrated longer duration of response and a survival advantage for responders in the higher dose arm, but no overall survival results were reported (Gralla et al, 1981). However, three subsequent larger randomized studies have failed to show advantage for the higher cisplatin doses, and toxicity was considerably worse (Klastersky et al, 1986;Gandara, 1993;Felip et al, 1997).…”
mentioning
confidence: 99%